Nonlinear dynamics of atomic and molecular systems in an electromagnetic field: Deterministic chaos and strange attractors - Бакуніна, Олена Валеріївна; Бакуніна, О. В.; Бакунина, Елена Валерьевна; Bakunina, Olena V.; Bakunina, Elena V.; Глушков, Олександр Васильович; Глушков, О. В.; Глушков, Александр Васильевич; Hlushkov, Oleksandr V.; Glushkov, Alexander V.; Ігнатенко, Ганна Володимирівна; Ігнатенко, Г. В.; et al. (Springer Nature, 2022)
We present a new mathematical approach to studying deterministic chaos and strange attractors in dynamics of nonlinear processes in atomic and molecular systems in an electromagnetic field. To treat chaotic dynamics of systems it is constructed effective scheme that includes new quantum-dynamic models (based on the finite-difference solution of the Schrödinger equation, optimized operator perturbation theory and realistic model potential for quantum systems) and advanced nonlinear analysis and a chaos theory methods such as power spectrum analysis, the correlation integral algorithm, the fractal method, the Lyapunov’s exponents and Kolmogorov entropy analysis, etc. Availability of multiple resonances with super little widths in spectrum of an atom in external magnetic field is treated and provided by interference phenomena and fluctuations. Dynamics of resonances in spectrum of diatomic molecule in the infrared electromagnetic field is considered and the topological and dynamical invariants are recalculated.

Представлено новий математичний підхід до вивчення детермінованого хаосу та дивних атракторів у динаміці нелінійних процесів в атомних і молекулярних системах в електромагнітному полі. Для обробки хаотичної динаміки систем побудована ефективна схема, яка включає нові квантово-динамічні моделі (на основі скінченно-різницевого рішення рівняння Шредінгера, оптимізованої теорії збурень оператора та реалістичного модельного потенціалу для квантових систем) і розширеного нелінійного аналізу та методу теорії хаосу, такі як аналіз спектру потужності, алгоритм кореляційного інтеграла, фрактальний метод, показники Ляпунова та ентропійний аналіз Колмогорова тощо. Наявність множинних резонансів із надмалими ширинами в спектрі атома в зовнішньому магнітному полі розглядається і забезпечується інтерференційними явищами та флуктуаціями. Розглянуто динаміку резонансів у спектрі двоатомної молекули в інфрачервоному електромагнітному полі та перераховано топологічний та динамічний інваріанти.
Glushkov A. V. Nonlinear dynamics of atomic and molecular systems in an electromagnetic field: Deterministic chaos and strange attractors / F. V. Glushkov, A. V. Ignatenko, A. A. Kuznetsova et al.// DSTA : Springer Proceedings in Mathematics and Statistics. - Vol. 363. - Springer Nature, 2022. - P. 113-123. Doi:10.1007/978-3-030-77310-6_11
Keywords: nonlinear dynamics; atomic systems; electromagnetic field; chaos; resonances; нелінійна динаміка; атомні системи; електромагнітне поле; хаос; резонанси; Research Subject Categories::TECHNOLOGY